Torticollis as the Presenting Sign of Cervical Spondylodiscitis. - Pizzol, Antonio; Bramuzzo, Matteo; Pillon, Roberto; Taddio, Andrea; Barbi, Egidio (Pediatr Emerg Care, 2016)
Acquired torticollis is a common clinical finding in children evaluated in the pediatric emergency department. It may be the presentation symptom of different illnesses, such as trauma, muscle contraction, infections, or malignancies, and an accurate differential diagnosis is required to correctly identify the cause and choose the right treatment. Spondylodiscitis is a low-grade bacterial infection that involves intervertebral disks and the adjacent vertebral bodies. Spondylodiscitis of the cervical spine is unusual and may be a rare cause of torticollis. We report the case of a 4-year-old male patient admitted to the emergency department for a 5-day history of painful torticollis. Blood tests showed an elevated erythrocyte sedimentation rate. The radiograph of the cervical spine showed a thin fifth cervical soma. The magnetic resonance imaging of cervical spine showed the alteration of cervical vertebral bodies and intervertebral disks, suggesting the diagnosis of cervical spondylodiscitis. The patient recovered after endovenous antibiotic treatment. We suggest that cervical spondylodiscitis should be suspected and investigated by means of an magnetic resonance imaging in every case of unexplained torticollis with persisting symptoms.